2018
DOI: 10.3102/0013189x17752928
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With “Acute” Food Insecurity Among College Students

Abstract: This study sought to understand which racial/ethnic student groups experience food insecurity and the extent to which other external insecurities and challenges are predictive of acute food insecurity. Data were derived from the Community College Success Measure (CCSM), an institutional needs assessment tool used by colleges to examine challenges facing underserved students. Findings from this research demonstrated that multiethnic and Black students are most likely to experience food insecurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 2 publications
1
36
0
Order By: Relevance
“…Students who identify as White are much less likely to experience food insecurity under the USDA criteria than non‐White students (39.6% of whom are food insecure, vs. 21.4% of White‐identifying students, X 2 (1, N = 320) = 11.013, p < 0.001). This is similar to what others have found as well (e.g., El Zein et al 2017; Martinez, Maynard, and Ritchie 2016; Mirabitur et al 2016; Wood and Harris 2018).…”
Section: Money: Spending Deals and Budgetingsupporting
confidence: 91%
See 1 more Smart Citation
“…Students who identify as White are much less likely to experience food insecurity under the USDA criteria than non‐White students (39.6% of whom are food insecure, vs. 21.4% of White‐identifying students, X 2 (1, N = 320) = 11.013, p < 0.001). This is similar to what others have found as well (e.g., El Zein et al 2017; Martinez, Maynard, and Ritchie 2016; Mirabitur et al 2016; Wood and Harris 2018).…”
Section: Money: Spending Deals and Budgetingsupporting
confidence: 91%
“…Financial issues appear to be an important component of food insecurity for students (Henry 2017), potentially exacerbated by changes in college funding and financial aid policies at the state and national levels (Martinez, Maynard, and Ritchie 2016) or student spending patterns (Hughes et al 2011), including higher personal expenditures on transportation, entertainment, shopping, or eating out (Chaparro et al 2009). Hughes et al (2001, 31) argue “university students appear to be at risk of food insecurity, both as a product of their socioeconomic and demographic attributes, and also as a result of an apparent misalignment of government policy that promotes tertiary [post‐secondary] education participation with inadequate financial and other student supports.” This suggests that financial barriers are tied to other structural factors, potentially making some college students more likely to experience food insecurity, including students who are Black (El Zein et al 2017; Wood and Harris 2018) or disabled (Booth and Anderson 2017). However, it also suggests that students as a group are likelier than the general population to experience food insecurity due to the context of funding and aid policies, and this is reflected in the higher rate of student food insecurity when compared with the general population using the USDA measure.…”
Section: Introductionmentioning
confidence: 99%
“…Soladavini et al 29 found that international students had greater odds of experiencing food insecurity as well as finding students that had more part‐time jobs and those receiving financial aid had higher odds of food insecurity. Another study related to college students found that African American or multi‐ethnic students were more likely to experience food insecurity 30 . Lastly, a study in Hawaii also found 21% of their students were food insecure and an additional 21% were at risk for food insecurity 31 .…”
Section: Discussionmentioning
confidence: 98%
“…The report by Goldrick-Rab et al (2019) referenced earlier indicated that at 123 2-year and 4-year colleges and universities, 50% of Latinx/a/o students reported experiencing food insecurity and 61% indicated encountering housing insecurity, compared to 39% and 51% of White students respectively. Additionally, one study of 6,103 students at California community colleges found an association between the challenges that Latinx/a/o students face in other aspects of their life (e.g., health concerns, transportation problems) and basic needs insecurity (Wood & Harris, 2018). As indicated earlier in the range of results in national studies, the prevalence of Latinx/a/o student food insecurity varies according to the type of institutions represented a given sample.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the affordability of postsecondary education has declined, students increasingly lack access to stable housing (e.g., Goldrick-Rab et al, 2017, 2019; Hallett & Crutchfield, 2017; Hallett & Freas, 2018) and to healthy food (e.g., Freudenberg et al, 2019; Patton-López et al, 2014; Phillips et al, 2018; Wood & Harris, 2018). Lacking basic housing and healthy food is associated with negative effects on academic, health, and social outcomes (Allen & Alleman, 2019; Hickey et al, 2019; Ilieva et al, 2019; Phillips et al, 2018).…”
mentioning
confidence: 99%